Gender Differences of the Mastication Patterns in Humans - Khamnei, S.; Zamanlu, M.; Shakouri, S.K.; Oskoee, S.S.; Salarilak, Sh.; Houshyar, Y.; Salekzamani, Y. (Нейрофизиология, 2016)
Nineteen young healthy subjects were offered a morsel of the hard (walnut) and soft (cake)
food, while surface EMG was recorded bilaterally from the masseter muscles. The duration
of the entire sequence of chewing, chewing rate, number of chewing cycles, time/cycle ratio,
and mean and maximum EMG amplitudes of the above muscles were compared in women
and men (n = 12 and 7, respectively). The duration of the whole chewing sequence for the
soft food and duration of a single chewing cycle for both food types were significantly longer
in women (P = 0.000). The masticatory frequencies for both food types were significantly
greater in men (soft food: 0.98 ± 0.18 and 1.79 ± 0.18 sec–1, hard food: 1.25 ± 0.29 and 2.03 ±
± 0.32 sec–1 in women and men, respectively; P = 0.000). The numbers of chewing cycles for
both food types were statistically similar (P = 0.38 and P = 0.67). The mean and maximum
EMG amplitude were found to be nearly similar in women and men, except for the mean
amplitude of the right EMG at soft food chewing was significantly higher in men (P = 0.02).
Thus, chewing in women occurs, in general, more slowly, while masseter muscle activities are
rather similar. The food consistency exerts a mild overall influence on the gender differences
of chewing. 19 молодим здоровим випробуваним пропонували з’їсти невелику порцію твердої (волоський горіх) або м’якої (торт)
їжі; в цей час відводили білатерально ЕМГ-активність жувальних м’язів. Тривалість усього епізоду жування, частота жувальних рухів, кількість жувальних циклів, тривалість
окремого циклу, а також середні та максимальні амплітуди
ЕМГ, відведених від вказаних м’язів, порівнювали у жінок
і чоловіків (n = 12 і 7 відповідно). Тривалість усього епізоду жування м’якої їжі та тривалості окремого циклу для
їжі обох типів були вірогідно більшими у жінок (P = 0.000).
Частоти жувальних рухів для їжі обох типів були значно
вищими у чоловіків (м’яка їжа: 0.98 ± 0.18 і 1.79 ± 0.18 с–1,
тверда їжа: 1.25 ± 0.29 і 2.03 ± 0.32 с–1 у жінок і чоловіків відповідно; P = 0.000). Число циклів жування для їжі
обох типів не демонструвало вірогідної різниці (P = 0.38 і
P = 0.67). Середня і максимальна амплітуди ЕМГ були майже однаковими у жінок і чоловіків. Єдиним винятком була
вища амплітуда ЕМГ справа у чоловіків при жуванні м’якої
їжі (P = 0.02). Таким чином, жування у жінок відбувається
в цілому повільніше, в той час як м’язова жувальна активність у представників різних статей є досить подібною. Консистенція їжі в цілому слабко впливає на гендерні відмінності процесу жування.